The Role of Dividend Policy in Explaining Corporate Governance and Profitability on Firm Value - Yenny Dwi Handayani; Ewing Yuvisa Ibrani (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
This study aims to determine the effect of corporate governance and profitability on dividend policy based on substitution theory and/or outcome theory in the banking sector in Indonesia. Theoretically, this study contributes which theory is more dominant between substitution theory and outcome theory by linking the influence of corporate governance with dividend policy and providing information about the impact of the application of the theory on firm value and build awareness to be careful of investors. Investors in making investment decisions, especially in the banking industry in Indonesia. In addition, this study also examines the role of dividend policy in explaining the relationship between corporate governance and profitability on the value of banking firms. A sample of 135 observational data comes from 27 banking companies during 2016-2020. This research found that corporate governance has a negative and significant influence on dividend policy. In addition, the CG index is one of the factors that can explain the company's market value. Profitability is empirically proven to influence dividend policy. Dividend policy is proven to play a role in mediating the relationship between profitability and firm value. However, it is empirically proven that dividend policy cannot mediate the relationship between corporate governance and firm value.